Pemberdayaan Masyarakat di Daerah Aliran Sungai Melalui Pengembangan Usaha Budaya Ikan Patin (Pangasius sp.) - Eny Budi Sri Haryani; Catur Paramono Adi; Aris Kabul Pranoto; Pola S.T. Panjaitan; Anasri Tanjung (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2022)
The Citarum watershed in Karawang has not been used productively to empower the community. How to use the Citarum watershed for fish cultivation is an important issue. The purpose of this study was to determine: (1) the socio-economic conditions of the community around the Citarum watershed and the level of technology adoption; (2) the potential and utilization of catfish (Pangasius sp.) cultivation ponds around the Citarum watershed; (3) condition of community institutions and policy recommendations for community empowerment. Data was collected through interviews, observations and literature studies with the determination of respondents purposive random sampling. The results of the study: (1) socio-economic conditions and the level of community technology adoption support for catfish cultivation; (2) the potential for catfish culture ponds is open and can be developed; (3) adequate community institutions, but need capital support (soft loans), so that regulations are needed to facilitate permits for land use for catfish farming ponds, continuous institutional building and professional business development.